IDENTIFIKASI DAN UJI AKTIVITAS ANTIKANKER EKSTRAK SPONS Ianthella basta TERHADAP LARVA Artemia salina L. - Sukmarianti, Ni Wayan Sri; Suaniti, Ni Made; Swantara, I Made Dira (CAKRA KIMIA (Indonesian E-Journal of Applied Chemistry), 2013)
The main purpose of this research is to determine the toxicity of extracts sponge Ianthella basta against Artemia salina larvae and to identify the chemical compounds contained in those toxic isolates. The preliminary test of the anticancer activity has conducted by Brine Shrimp Letalithy (BST) test. The results showed that the chloroform extract was the most toxic with LC 50 value of 22,39 ppm. Futher, the cloroform extract was separated and purified by coloumn chromatography using eluent of solvent mixture of chloroform : ethyl acetate : n-hexane by 7 : 2 : 1 and 4 fractions were obtained. The most toxic fraction was the fraction C with LC 50 value of 35,36 ppm. Based on the GC-MS results, the toxic isolate is allegedly containing chemicals compound of hexadecanoic methyl ester and hexadecanoic acid.
Keywords: Ianthella basta, toxicity test, anticancer activity